2020
DOI: 10.1111/jonm.13082
|View full text |Cite
|
Sign up to set email alerts
|

What makes experienced nurses stay in their position? A qualitative interview study

Abstract: Aim To explore which factors are important in experienced nurses’ intention to stay in the clinical setting and to learn which factors affect their job satisfaction. Background Nursing turnover is a challenge for health care quality outcomes, and retaining nursing expertise at the bedside is of great importance. Thus, we must understand why nurses choose to stay employed in their clinical settings. Method(s) Twenty‐eight nurses participated in a qualitative interview study. The data were analysed using inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 29 publications
3
28
0
1
Order By: Relevance
“…Nearly half of the participants were post-90s nurses, and 52.5% of nurses' working experience was below ten years; thus, caring for COVID-19 patients is a highly stressful and difficult job for nurses. This finding is consistent with that of Loft and Jensen (Loft & Jensen, 2020) which indicates that nurses may feel uneasy about career challenges, so they may consider whether or not to stay in their job. Interestingly, recent evidence has shown that employees were using the experience of post-traumatic growth to rebuild their self-concept and raising a sense of openness and optimism about what they can do, which may prompt them to pursue new roles and vocations (Vogel & Bolino, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nearly half of the participants were post-90s nurses, and 52.5% of nurses' working experience was below ten years; thus, caring for COVID-19 patients is a highly stressful and difficult job for nurses. This finding is consistent with that of Loft and Jensen (Loft & Jensen, 2020) which indicates that nurses may feel uneasy about career challenges, so they may consider whether or not to stay in their job. Interestingly, recent evidence has shown that employees were using the experience of post-traumatic growth to rebuild their self-concept and raising a sense of openness and optimism about what they can do, which may prompt them to pursue new roles and vocations (Vogel & Bolino, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…The more professional benefits nurses perceive, the stronger their intrinsic motivation. As a result, these nurses see nursing as a unique profession rather than a job, because it offers immersion and development opportunities, so that they would persist in their careers (Loft & Jensen, 2020;Wu et al, 2019). What leads to growth is not the rescue experience, but how the frontline nurses interpret and respond to this experience.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a positive connection between GPs` WLB and their motivation to stay in the profession, which matches with similar results in nurses and academics [ 30 , 31 ]. In addition, research on health professionals connect better WLB to a reduced intention to leave the job [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…
There seems to be a link between the goods nurses strive to achieve on their own behalf and their remaining in practice (Kristoffersen, 2019;Loft & Jensen, 2020). It has been reported that nurses who remain in practice want to create something good for themselves-they want to improve themselves as human beings to become better persons, indicating they are oriented towards themselves (Kristoffersen & Friberg, 2015).
…”
mentioning
confidence: 99%